2002
DOI: 10.1063/1.1465531
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different types of threading dislocations on the carrier mobility and photoluminescence in epitaxial GaN

Abstract: High-resolution x-ray diffraction has been used to analyze the type and density of threading dislocations in a series (0001)-oriented GaN epitaxial film. Photoluminescence (PL) and carrier mobility of the films are measured at room temperature. The intensities of both the band edge (3.42 eV) peak and yellow luminescence (YL) are strongly related to the threading dislocation density of the GaN films. But different types of dislocations show different relationship with the intensities of PL and YL. The fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
47
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 15 publications
(22 reference statements)
3
47
0
Order By: Relevance
“…However, it has only recently been realised that the edge and screw nature of the threading dislocations has an influence on the band edge and yellow photoluminescence [2]. In their seminal transmission electron microscopy and high-resolution X-ray diffraction study, Metzger et al [3] demonstrated clearly the connection of threading edge dislocations to in-plane mosaic and threading screw dislocations to out-of-plane mosaic.…”
mentioning
confidence: 98%
“…However, it has only recently been realised that the edge and screw nature of the threading dislocations has an influence on the band edge and yellow photoluminescence [2]. In their seminal transmission electron microscopy and high-resolution X-ray diffraction study, Metzger et al [3] demonstrated clearly the connection of threading edge dislocations to in-plane mosaic and threading screw dislocations to out-of-plane mosaic.…”
mentioning
confidence: 98%
“…5 Highresolution x-ray diffraction studies of GaN layers have indicated that both carrier mobility and the intensity of photoluminescence are strongly related to defects. 6 It was also observed that a phase transformation from wurtzite ͑WZ͒ to rock-salt structure can be induced by high pressure in GaN. 7 However for GaN nanostructures, surface stresses due to high surface-to-volume ratios are another factor that may lead to structural transitions.…”
mentioning
confidence: 99%
“…To study the size effect, rods with different cross-sectional diameters ͑d = 22. 6 lent semiconductor with significant ionic characteristics, 13 a set of interatomic pair potentials 14 consisting of a long-range Coulombic part and a short-range part is used to describe the Ga-Ga, N-N and Ga-N interatomic interactions. The calculation of long-range Coulomb force uses direct summation without any cutoff in order to accurately describe chargecharge interactions.…”
mentioning
confidence: 99%
“…In particular, extremely high TDDs can drastically degrade the internal quantum efficiency [2,3], mobility [4] and the carrier concentration [5] in LEDs. Several methods of fabricating high-quality templates have been reported; for example, the use of AlN/AlGaN super lattices (SLs) grown with alternating gas-feeds [6], AlGaN templates deposited by epitaxial lateral overgrowth [7], and a combination of GaN/AlN SLs and AlGaN produced by alternating-source-feed epitaxy on SiC [8].…”
mentioning
confidence: 99%